Coexistance of different damage-associated myeloid populations in the hippocampus of Alzheimer's patients - Sánchez-Mejías, Elisabeth; Mejías-Ortega, Marina; Dávila-Cansino, José Carlos; Gutiérrez-Pérez, Antonia; Vitorica Ferrández, Javier (Wiley, 2021)
Parenchymal microglia are the brain-resident immune cells capable of responding to damage. Though the role of microglial cells in the development/progression of AD is still unknown, a dysfunctional response has recently gained support since the identification of genetic risk factors related to microglial. In this sense, we reported an attenuated microglial activation in the hippocampus of AD patients, including a degenerative process of the microglial population in the dentate gyrus. On the other hand, it is also known that others myeloid components could also be involved in the neurodegenerative process. However, the implication of the diverse immune cells in the human pathology have not been determined yet. In this work, we analyzed the phenotypic profile displayed by damage-associated myeloid cells in the hippocampus of AD brains. For this purpose, immunohistochemistry and image analysis approaches have been carried out in non-demented controls and AD cases. Damage-associated myeloid cells from Braak II and Braak VI individuals were clustered around amyloid plaques and expressed Iba1, TMEM119, CD68, Trem2 and CD45high. A subset of these cells also expressed ferritin. However, and even though some Braak II individuals accumulated CD45-positive plaques, only AD patients exhibited parenchymal infiltration of CD163-positive cells, along with a decrease of the resident microglial marker TMEM119. Moreover, a negative correlation was observed between CD163 and TMEM119 intensities in Braak VI patients, showing a functional cooperation among these different myeloid populations. Taken together, these findings suggest the existence of different populations of amyloid-associated myeloid cells in the hippocampus during disease progression. The differential contribution of these myeloid populations to the pathogenesis remains to be elucidated. The dynamic of the myeloid molecular phenotypes associated to AD pathology needs to be considered for guarantee clinical success.
Keywords: Biología celular; Genética; Alzheimer; Alzheimer; Microglia; Mieloide; Neuroinflamación